A STUDY OF SAVINGS AND INVESTMENT PATTERN OF SEMI-MEDIUM AND MEDIUM FARMERS WITH SPECIAL REFERENCE TO WESTERN MAHARASHTRA PLAIN ZONE - LITERATURE REVIEW - Snehal J. Mirajkar,; Avadhoot Pol, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
India is an agricultural country. Around 60% population in India is living on agriculture. Agriculture is the main contributor to the GDP of India. Agriculture helps in the development of the economy as well as the reduction in poverty by increasing employment. It also provides food security for people in India. Therefore, Agriculture is the most growing sector in India. Farmer's savings and investment pattern plays important role in the development of the Indian economy. Good savings and investment programs lead to a) improvement in the allocation of resources, b) promotion of equal distribution of income, and c) reduction in cost and cost period. The data for this research is collected from various related research papers, articles, the government publishes, etc. This research review is beneficial to understand the existing pattern of savings and investment of farmers.